Marcus Aurelius, a biography - Birley, Anthony Richard (Routledge, 2000)
Marcus Aurelius, the philosopher-emperor who ruled the Roman Empire between AD 161 and 180, is one of the best recorded individuals from antiquity. Even his face became more than usually familiar: the imperial coinage displayed his portrait for over 40 years, from the clean-shaven young heir of Antonius to the war-weary, heavily bearded ruler who died at his post in his late fifties. His correspondence with his tutor Fronto, and even more the private notebook he kept for his last ten years, the Meditations, provides a unique series of vivid and revealing glimpses into the character.